Factors influencing residents' subjective well-being at World Heritage Sites. (December 2017) - Chi, Christina Geng-qing; Cai, Ruiying; Li, Yongfen
Abstract: This study aims to identify the factors influencing residents' subjective well-being (SWB) and examine the relative importance of each factor on the distinct components of residents' SWB in the heritage tourism context. The measurement was developed and validated using rigorous procedures. Five rounds of data collection have occurred in a span of two years at a World Heritage Site in China, resulting in 1018 valid responses. Data were analyzed and the results suggested that residents with higher economic status, sense of community, and social environment generally have higher SWB. Furthermore, residents' perceived high economic status and favorable social relations channel through residents' SWB to bolster their support for tourism. Highlights: This study involved 5 rounds of data collection from 1018 local residents in a span of two years at a World Heritage Site. Six factors were identified as the major factors influencing residents' subjective well-being (SWB). Residents with higher perception of economic status, sense of community, and social environment generally have higher SWB. Residents' perceived high economic status and favorable social relations bolster their support for tourism via their SWB. Residents' SWB had strong power in explaining their support for tourism.